Impact of Immunosenescence on Immune‐Related Adverse Events in Elderly Patients With Cancer - Jiayi Gao; Yue Yuan; Xue Wang; Liuer He; Lin Li (Aging Medicine)
ABSTRACT Immune checkpoint inhibitors (ICI), have transformed the management of several types of cancers; however, immune‐related adverse events (irAEs) may cause treatment interruptions, chronic toxic effects, and death. Elderly patients are at high risk of cancer. Compared with traditional chemotherapy, immunotherapy has become a better alternative choice for elderly patients with cancer due to its high efficiency and low toxicity. However, the emergence of immunosenescence accompanied by advancing age raises safety concerns for ICI. Therefore, we summarize the characteristics of irAEs occurred in elderly patients with cancer and the physiological characteristics of immunosenescence, which will lay a theoretical foundation for the safety management of immunotherapy in elderly patients with cancer.